An approximation method for common fixed points of a finite family of asymptotic pointwise nonexpansive mappings - Nanjaras,B. (Springer Publishing Company, 2015)
In this article, we consider an iterative scheme to approximate a common fixed point for a finite family of asymptotic pointwise nonexpansive mappings. We obtain weak and strong convergence theorems of the proposed iteration in uniformly convex Banach spaces. The related results for complete CAT(0) spaces are also included. © 2012 Nanjaras and Panyanak; licensee Springer.